STRATEGI PENGELOLAAN PERKAMPUNGAN BUDAYA BETAWI SETU BABAKAN SEBAGAI DESTINASI WISATA PADA MASA NEW NORMAL - Yovi Nurhalimah; Budiaman; Nova Scorviana (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to find out the reasons and strategies for managing the PBB Setu Babakan as a tourist destination during the new normal period. The research was conducted in the PBB Setu Babakan tourist area. This study uses a descriptive method with a qualitative approach, while data collection techniques include observation, interviews, literature study, and documentation. Data analysis using the interactive data analysis model by Miles and Huberman. The subject of this research is the managing member of PBB Setu Babakan. The results of the study show that a management strategy is needed for internal reasons, namely to maintain assets, quality of attractions, facilities and destination services that are in accordance with tourist destinations to provide maximum satisfaction to visitors, as well as external reasons due to facing new demands of the tourism sector and changes in people's behavior in conducting tourism activities. The management strategy is based on management principles. In planning, managers identify supporting/inhibiting factors in achieving management objectives and strategies for overcoming them and develop strategies for managing destinations and controlling activities. Organizing includes setting responsibilities, working with partners, and UMKM training. Implementation includes developing destinations, increasing SDM competencies, strengthening tourism institutional capacity, as well as promotion through digital and conventional media. Evaluation is carried out through community satisfaction surveys, work meetings, and community quick responses. Even though there has been no ecological contribution and an increase in investment volume due to a lack of profit, the indicators of successful management have been fulfilled.